Perforated Subhepatic Appendix Presenting as a Gas under Diaphragm: Clinical Diagnostic Challenges for Surgical Residents: A Case Report - Yadav, Dipak Kumar; Gautam, Bhesraj; Bhattarai, Amit; Poudel, Saurav; Bhattarai, Ashish (Journal of Nobel Medical College, 2023)
This study addresses the rarity of the subhepatic location of the appendix, found in only 0.08% of cases, and the infrequent occurrence of perforated appendicitis presenting with gas under the diaphragm. When these two uncommon conditions coincide in the context of one of the common causes of acute abdomen, namely acute appendicitis, it poses a diagnostic challenge for surgical residents in training. The case presented involves a patient with generalized abdominal pain, soft abdomen, and tenderness over all quadrants, particularly the right upper quadrant. Her chest x-ray findings indicated free gas under the right hemi-dome of the diaphragm and an inconclusive ultrasound for acute appendicitis, computed tomography confirmed the subhepatic appendix and pneumoperitoneum. Operative intervention revealed a perforated subhepatic appendix, and the patient recovered well, being discharged on the 4th postoperative day. The clinical discussion emphasizes the ability of surgical residents to safely perform appendectomies but highlights the crucial role of experienced surgeons in managing cases with atypical presentations. The conclusion underscores the diagnostic challenges posed by atypical presentations of acute appendicitis in a clinical setting.